2020
DOI: 10.1186/s12889-020-08970-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diabetes prevalence and corresponding risk factors - findings from 3- and 6-year follow-up of PURE Poland cohort study

Abstract: Background: Diabetes mellitus (DM) is one of the greatest challenges for public health worldwide. The aim of the study was the analysis of diabetes development in participants with normoglycemia and Impaired Fasting Glucose (IFG) in 3-year and 6-year follow-up of PURE Poland cohort study. Methods: The analysis was conducted in Polish cohort enrolled into Prospective Urban and Rural Epidemiology (PURE) Study. The following study presents results of 1330 participants that have partaken both in the baseline study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Mitigating inequalities in the health condition of the inhabitants of Central and Eastern Europe, as with the example of the Janów Lubelski district analysed in our research, is an essential priority in advancing the goal of sustainable development for Poland and the European Union. 103 Given that the incidence of MetS has been increasing in recent years, 104 , 105 identifying a population at risk of MetS would be associated with a more effective screening policy and with prevention too (primary and secondary). Our research showed that people in rural areas were more likely to develop MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Mitigating inequalities in the health condition of the inhabitants of Central and Eastern Europe, as with the example of the Janów Lubelski district analysed in our research, is an essential priority in advancing the goal of sustainable development for Poland and the European Union. 103 Given that the incidence of MetS has been increasing in recent years, 104 , 105 identifying a population at risk of MetS would be associated with a more effective screening policy and with prevention too (primary and secondary). Our research showed that people in rural areas were more likely to develop MetS.…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, 8% of the population suffers from diabetes and it is estimated that 25-30% of adults with diabetes are unaware of their health condition. the prediction shows that diabetes prevalence in Poland will be 11% by 2040 [2]. In the Costa Rican population, the same trend is observed.…”
mentioning
confidence: 61%
“…In our study, we have assessed the risk of diabetes development by calculating the FINDRISC score in baseline population without diabetes and compared those results with occurrence of diabetes after 6 years of observation. Although the FINDRISC score has been originally validated to assess the 10-year risk of diabetes development, 7 due to the high increase in diabetes prevalence in our cohort during 6 years of observation 12 we decided to check if the FINDRISC score was predictive of this outcome. Our results show that the FINDRISC score was significantly higher at the baseline in those who progressed to diabetes after 6 years, than in those who remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Although the FINDRISC score has been originally validated to assess the 10-year risk of development of diabetes, 7 it has been previously used in 7-year or 9-year assessments of diabetes risk. [9][10][11] The prevalence of diabetes increased rapidly over 6 years of observation of the PURE Poland cohort study, 12 hence the decision to check if the FINDRISC score assessed at the baseline predicted the diabetes development in this study period.…”
Section: Introductionmentioning
confidence: 99%